2019
DOI: 10.1021/acs.iecr.9b02829
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physicochemical Characterization of Shaped Catalysts of β and Y Zeolites for Cyclization of Citronellal

Abstract: Continuous cyclization of citronellal over zeolite-based extrudates was performed in a trickle-bed reactor at 35−70 °C and 10 bar of argon. Catalytic results were correlated with the physicochemical properties of the shaped catalyst prepared by extrusion of β or Y zeolites with binders. Rheological tests were used to elucidate the flow properties of a catalytic slurry and relate them with the extrusion performance. This study revealed that application of methylcellulose and bentonite binder modified the textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 56 publications
7
50
0
Order By: Relevance
“…One of the explanations is that the cyclization diastereoselectivity is determined by thermodynamics. 6,19,25 When comparing the stereoselectivity to menthol reported in the literature 4 over Ru/H-beta-35, 75% stereoselectivity to menthol at nearly full conversion was obtained after 180 min. 4 It should be pointed out that the results are not directly comparable, because in the literature 4 the reaction was performed at 100°C under 25 bar using a citronellal to Table 7 Crushing strength of extrudates in vertical and horizontal positions catalyst mass ratio of 9 : 1, whereas in the current case the reaction was performed at 10 bar total pressure in a H 2 atmo-sphere and 35°C with a citronellal to catalyst mass ratio of 1.2 : 1.…”
Section: In Which the Reaction Was Performed At 100°cmentioning
confidence: 94%
See 2 more Smart Citations
“…One of the explanations is that the cyclization diastereoselectivity is determined by thermodynamics. 6,19,25 When comparing the stereoselectivity to menthol reported in the literature 4 over Ru/H-beta-35, 75% stereoselectivity to menthol at nearly full conversion was obtained after 180 min. 4 It should be pointed out that the results are not directly comparable, because in the literature 4 the reaction was performed at 100°C under 25 bar using a citronellal to Table 7 Crushing strength of extrudates in vertical and horizontal positions catalyst mass ratio of 9 : 1, whereas in the current case the reaction was performed at 10 bar total pressure in a H 2 atmo-sphere and 35°C with a citronellal to catalyst mass ratio of 1.2 : 1.…”
Section: In Which the Reaction Was Performed At 100°cmentioning
confidence: 94%
“…The synthesis of shaped Pt-and Ru-extrudates containing 30 wt% aluminosilicate clay bentonite from VWR International as a binder was the same as the previously published procedure. 18 Based on the previous studies, [18][19][20] the zeolite/ binder weight ratio of 70/30 has been found suitable for easy shaping of the catalyst by extrusion to achieve strong and stable extrudates. All materials were crushed and sieved into a fraction <63 μm in a vibratory micro mill (Fritsch).…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive was the inclusion of bentonite or methylcellulose as binders on shaped βand Y zeolites for cyclization of the lemon-like odor citronellal into menthol-like odor pulegol products in continuous mode. [32] Despite certain mass-transfers limitations and altered acid properties the final (sum of isomer) products yield was not severely affected. [32] Not only the binder choice matters, but also the preparation method does when tailoring shaped catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Despite certain mass-transfers limitations and altered acid properties the final (sum of isomer) products yield was not severely affected. [32] Not only the binder choice matters, but also the preparation method does when tailoring shaped catalytic systems. Zecevic et al reported improved catalytic performances on hydrocracking reactions for bifunctional PtÀ Y zeolite catalysts incorporating the metal phase on the binder (Al 2 O 3 in that case) rather than on the zeolite, being the distance between active phases the key for such improvement.…”
Section: Introductionmentioning
confidence: 99%